Pengembangkan dan Memonitoring Tanaman Hidroponik dan Saluran Pengairan Sawah di Lembang Randan Batu - Nova Ria Sar; Romoldus W. Samiu; Randi Tangdialla (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This service aims to develop and monitor hydroponic plants in an effort to increase agricultural efficiency in Lembang Randan Batu. The hydroponic farming method was chosen as a solution to increase agricultural efficiency by utilizing water optimally and reducing land use. Apart from that, cleaning of rice field irrigation channels is carried out to reduce environmental pollution due to plastic waste. This research uses the method of selecting plants, creating a hydroponic system, planting and maintaining plants, collecting plastic waste, sorting and processing plastic waste. The research results show that hydroponic plants can grow well and provide satisfactory results, while cleaning rice field irrigation channels can reduce environmental pollution due to plastic waste. This service contributes to the development of sustainable agriculture and plastic waste management in Lembang Randan Batu.